THIRD RESEARCH AND EDUCATIONAL CONFERENCE OF CAUCASIAN CARDIOLOGISTS AND INTERNAL MEDICINE SPECIALISTS OCTOBER 29–30TH 2013, VLADIKAVKAZ (Кардиоваскулярная терапия и профилактика)
Third Research and Educational Conference of Caucasian Cardiologists and Internal Medicine Specialists October 29–30th 2013, Vladikavkaz.